Job Burnout Among Hotel Employees: The Impact on OCB and Employee Performance - Harjanti, Dhyah; Charistianty , Agatha (Journal of Applied Management and Business, 2024)
The company’s success is determined by employee performance. To ensure that the employees are able to deliver their best performance, the company must pay attention on various factors, for instance: job burnout. Job burnout often occurs among hotel employees. Hotels must operate resourcefully to deliver good quality service continuously. The tasks at the hotel are very demanding, and the work environment is stressful. Every employee is forced to be able to work multitasking rapidly and skillfully so that the hotel can operate effectively and efficiently. The research objective is to determine the impact of job burnout on employee performance by using organizational citizenship behavior as an intervening variable for hotel employees. In this quantitative research, a survey was conducted on 120 employees who worked in a number of two-star hotels in Surabaya. The sample was determined using a purposive sampling technique. The data obtained was processed using the Partial Least Square analysis technique. The research results show that job burnout can significantly disrupt employee performance and organizational citizenship behavior. Meanwhile, organizational citizenship behavior can significantly improve employee performance. Organizational citizenship behavior has also been proven to be able to act as a mediating variable in the relationship between job burnout and employee performance.